Updating for onliners - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The new bi-monthly CTA electronic newsletter ICT-Update is well underway, with its third issue planned for April 2001. It serves to keep people abreast of developments in the fast moving world of ICT (information and communication technologies)...